Forensic analytics using cluster analysis: Detecting anomalies in data. Issue 2 (15th January 2021) - Goh, Clarence; Lee, Benjamin; Pan, Gary; Seow, Poh Sun
Abstract: Cluster analysis is a data analytics technique that can help forensic accountants effectively detect anomalies in complex financial datasets. This article provides a description of clustering analysis, discusses how it can be implemented to detect anomalies in data, and illustrates its use through a worked example using the Tableau software.